Pengaruh Pendidikan Sekolah Minggu Buddhis (SMB) terhadap Perkembangan Fisik-Motorik Peserta Didik di SMB Sariputta Buddhist Studies Pekanbaru - Hadion Wijoyo; Sulaiman Girivirya (STAB Maitreyawira, 2020)
Buddhist Sunday School Education (SMB) is very closely related to the physical-motor development of SMB students who have a very broad understanding. SMB education has been provided with a good curriculum, shown with real evidence (with practice and has a purpose), service educators who are responsible by using the heart, and have responsive students. In addition, the use of teaching aids that are appropriate to the development of the situation, delivery methods that are on target, adequate environmental conditions, and material that is easily digested by students in accordance with the times, so that all can be conveyed properly in accordance with the physical-motor development of the participants SMB students by providing optimal results in the form of changes in student behavior. Therefore education must be able to understand changes in student behavior and provide results with the quality of students as expected by parents. SMB education that has vision, mission and quality in the eyes of parents is very important in attracting SMB students to continue learning and help the process of learning and harmony between students and educators so that there will be changes in student behavior. Thus SMB education is expected to have a positive effect on the physical-motor development of SMB students.